ANALISIS IMPLEMENTASI GOOD CORPORATE GOVERNANCE (GCG) DALAM MENINGKATKAN TRANSPARANSI DAN KEBERLANJUTAN TATA KELOLA PERUSAHAAN (Tinjauan Deskriptif pada PT Bukit Asam Tbk) - Risma Indriyanti; Teku Dede Ariyanto; Dian Ayu Puspita (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Good Corporate Governance (GCG) refers to effective, ethical and sustainable corporate governance. This study aims to analyze the implementation of GCG at PT Bukit Asam Tbk (PTBA), focusing on transparency and sustainability as reflected in the company's official reports. The method used is a document based descriptive review to assess the consistency and impact of GCG implementation. PTBA shows a strong commitment to GCG principles, namely transparency, accountability, responsibility, independence and fairness. The company also implements Good Mining Practice (GMP) principles, which emphasize compliance with regulations, as well as environmental, social, and safety responsibilities. Overall, PTBA has demonstrated consistent and sustainable GCG implementation.